Prioritization Strategy for Measures in the Brazilian Security Framework - Sousa, Marco Antonio Firmino de; Silva, Douglas Chagas da; Soares, Heder Dorneles (Anais do Latin American Symposium on Digital Government (LASDiGov); 2025: Anais do XIII Latin American Symposium on Digital Government, 2025)
This article presents the actions of the Brazilian government to build a sustainable model to address issues of information security, data protection, and privacy. It also presents the leading agencies involved, their responsibilities, and the transversality of their actions within these themes. A national framework is presented that aims to ensure compliance and assess the maturity of the federal administration in these themes, in addition to promoting a culture in these issues and being in compliance with national and international regulations and best practices. In addition, the Analytic Hierarchy Process (AHP) method is applied to a set of controls of the Brazilian framework, seeking to obtain priority measures for these controls. The results demonstrate the importance of correct and efficient judgment necessary to define and prioritize the measures implemented by the institutions in each control.